Lifestyle and dietary habits of high school going students in north-eastern part of Bangladesh during COVID-19 Pandemic - Sunny, Ahsan Habib; Chowdhury, Muhammad Sakib Ibtidha; Ullah, Mohammad Ohid (Asian Journal of Medical and Biological Research, 2021)
Food habits and lifestyle are risk factors of health problem. Moreover, adulthood health depends on adolescent health. A cross-sectional study was designed to know the lifestyle and dietary habits of high school going students during the pandemic. A semi-structured questionnaire was developed and data were collected randomly from the students. Descriptive analysis, logistic regression model and factor analysis were used to analyze the data. The results revealed that most of the students fairly follow the lifestyle and dietary habits. It is observed that students who read newspapers daily are 75% more likely to follow the dietary pattern. During a pandemic, most of the high school going students in north-eastern part of Bangladesh were taking protein types food (communality=0.724) and vegetables (communality=0.694) maximum times per week. Students increased their sleeping hours (communality=0.784) and intended to do job (communality=0.781) to help their families during the COVID-19. Moreover, the study also observed some important lifestyle factors like- watching mobile/laptop, connecting social media etc. and most of the students (45%) thought that electronic devices hamper their normal education. Taken together, the findings of this study may be useful to make awareness in the society about the healthy and unhealthy lifestyle as well as food habits. Government and Non-Government organizations should take proper nutritional and health related programs in the high schools that provide healthy lifestyle and food habits for improving the public health sector in Bangladesh. Asian J. Med. Biol. Res. 2021, 7 (4), 359-366